Sex Differences in Psychological Status and Fatigue of Frontline Staff After the COVID-19 Outbreak in China: A Cross-Sectional Study - Teng, Ziwei; Su, Yuhan; Chen, Jindong; Wu, Renrong; Tang, Hui; Wu, Haishan; Liu, Xuming; Ling, Heqiao; Yuan, Hui; Huang, Jing (Frontiers in Psychology, 2021)
Abstract Background: the coronavirus disease 2019 (COVID-19) is spreading globally, and it is significant to pay attention to the mental health of frontline staff in this pandemic. This study is aimed to explore the sex difference among the frontline staff in demographics, characteristics of mental state, and the potential relationship between them. Method: a total of 2614 Chinese frontline staff were recruited. The Self-Rating Anxiety Scale (SAS) and the Patient Health Questionnaire-9 (PHQ-9) are used for assessing the mental status of frontline staff, and the Fatigue Self-Assessment Scale (FSAS) is used for detecting fatigue. Result: the prevalence rate of anxiety for female frontline staff which is higher than that of male (P=0.003), and the prevalence rate of depression is similar between them (P=0.091). After comparing the risk factors of unhealthy mental state between different sex, it is found that family income below 100,000 [depression: odds ratio (OR) 1.37;95% confidence interval (CI),1.08-1.73; anxiety: OR 1.99;95% CI,1.44-2.75], unsupported of family (depression: OR 10.94; 95% CI, 1.39-85.79; anxiety: OR 11.92; 95% CI, 3.80-37.36) and marriage (depression: OR 1.67; 95% CI, 1.15-2.43) are risk factors for male, and total fatigue (depression: OR 2.96; 95% CI, 1.46-6.02) is risk factor for female. Conclusion: This study found that depression and anxiety are widespread among the frontline staff of COVID-19, and anxiety showed a higher prevalence rate among female frontline staff. From the sex difference in risk factors, it is possible that the focus of psychological interventions may differ between genders. Males with low family income, unsupported by family or marriage, and females with a high score of total fatigue require particular attention to their psychological status.